The Shortest and Longest Pregnancy Period According to Fiqh and Legislation of Muslim Countries - Trigiyatno, Ali (al-'adalah, 2022)
The Shortest and Longest Pregnancy According to Islamic Jurisprudence and Legislation of Muslim Countries. This study examines how long a woman's pregnancy takes according to fiqh Islamic Jurisprudence and legal provisions in several Muslim countries. This research is purely a literature study using a normative approach that refers to the provisions of family law in several Muslim countries. The legal analysis used is an authentic and doctrinal interpretation method. The fiqh scholars state that the shortest gestation period is six months, while the fiqh scholars differ in their opinion regarding the longest gestation period. Generally, they agree that the longest gestational age is six months. Although legal provisions in various Muslim countries often do not refer to the opinion of fiqh scholars who argue that the longest gestation period is more than one year. This research finds the fact that legislators in various Muslim countries do not use the classical scholar's opinion about pregnancy because it is considered unscientific and does not support social reality. Muslim countries generally define six months as the shortest period of pregnancy and one year as the longest, except for Brunei Darussalam which defines four years.